Analisis Karakteristik Kepemimpinan Transformasional di Madrasah Aliyah - Nurul Fika; Anis Fauzi; Anis Zohriah (Journal on Education, 2023)
This research uses qualitative research type methods with a library research approach, namely (library research) or literature studies by exploring information through literature regarding characteristics and transformational leadership to answer the focus of the study in this research. This study examines the definition of transformational leadership, the four dimensions of transformational leadership, the characteristics of transformational leadership and the measurement instruments of transactional and transformational leadership. Leadership is one of the most important things that everyone must have because oneself is actually a leader for our own body, for that leadership is very important. The characteristics of transformational leadership include: 1) Idealized influence (or charismatic influence) 2) Inspirational motivation. 3) Intellectual stimulation. 4) Individualized consideration.